2013
DOI: 10.1080/03235408.2013.822753
|View full text |Cite
|
Sign up to set email alerts
|

A comparative screening of hybrid, modern varieties and local rice cultivar for brown leaf spot disease susceptibility and yield performance

Abstract: Five rice cultivars, one hybrid (WR96), three modern (BR16, BR26, and BRRI Dhan27) and one local (Pari) were screened for reaction to brown leaf spot disease caused by Cochliobolus miyabeanus and performance of yield-related characters. The severity of brown leaf spot varied with growth stages of rice plant as well as different cultivars tested under field condition. Low disease severity was observed at maximum tillering stage compared to moderate to high at dough stage, with hybrid cultivar WR96 showing highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 13 publications
3
7
0
Order By: Relevance
“…Grain yield differences due to varieties were also reported by Biswas et al (1998). The results agreed with the findings of Sarker et al (2013); Hossain et al (2014); Shiyam et al (2014). The differences in straw yield among the varieties might be attributed to the genetic makeup of the varieties.…”
Section: Yield and Harvest Indexsupporting
confidence: 92%
See 2 more Smart Citations
“…Grain yield differences due to varieties were also reported by Biswas et al (1998). The results agreed with the findings of Sarker et al (2013); Hossain et al (2014); Shiyam et al (2014). The differences in straw yield among the varieties might be attributed to the genetic makeup of the varieties.…”
Section: Yield and Harvest Indexsupporting
confidence: 92%
“…The variation as assessed might be due to genetic characters of the varieties primarily influenced by the heredity. Sarker et al (2013) and Hossain et al (2014) also reported that panicle length varied among varieties.…”
Section: Panicle Lengthmentioning
confidence: 95%
See 1 more Smart Citation
“…The host plant's enhanced ability to mobilize its innate immunity or defence system against perceived plant pathogen is referred to as priming or induced systemic resistance (ISR) (Hossain et al 2007(Hossain et al , 2008b(Hossain et al , 2014aKojima et al 2013). ISR is considered one of the most efficient mechanisms of plant defence against invading plant pathogens.…”
Section: Induced Resistancementioning
confidence: 99%
“…(2014);Hossain et al (2014);Shiyam et al (2014);Sarker et al (2013); Baset Mia and Shamsuddin (2011);Jeng et al (2009) andBakul et al (2009) . They also found variation in panicle length due to the variation in genetic make-up of the varieties of rice.…”
mentioning
confidence: 99%